The Impact of Environment Accounting Information Disclosure on Enterprise Value - Zheng, Xinna (Journal of Roi Kaensarn Academi, 2024)
The objectives of this research were: 1) research results on the relationship between expanding and enriching corporate environmental accounting information disclosure and corporate value2) By using theoretical analysis, mathematical modeling and other methods, combined with qualitative and quantitative research conclusions, we strive to guide practice through theoretical research.The sample studied were 410 Chinese A-share Listed Companies from 2010 to 2020. They were selected by the database of Tai’ an. the research instrument for the data collection were StataSE 15.0. The statistics for data analysis were mean, analysis of variance, and Multiple regression analysis method. The research results were found as follows; 1)There is a significant U-shaped relationship between enterprise value and environmental accounting information disclosure. 2)The inflection point of the U-shaped relationship is 0.368. The suggestion were 1)strengthen the formulation of laws, regulations, and standards, establish corresponding review mechanisms, and promote transparent disclosure of environmental information by enterprises. 2)support enterprises to carry out technological innovation and improvement in clean production, resource utilization, energy conservation and emission reduction, and improve their environmental protection level.